2014
DOI: 10.5539/gjhs.v6n3p186
|View full text |Cite
|
Sign up to set email alerts
|

On Pump Coronary Artery Bypass Graft Surgery Versus Off Pump Coronary Artery Bypass Graft Surgery: A Review

Abstract: There are two basic ways of performing coronary artery bypass graft surgery (CABG): on pump CABG and off pump CABG. Off pump CABG is relatively a newer procedure to on-pump CABG and does not require the use of the cardiopulmonary bypass machine. On pump CABG is the more traditional method of performing bypass surgery. However its resultant inflammatory effects cause renal dysfunction, gastrointestinal distress and cardiac abnormalities which have forced the surgeons to look for alternatives to the procedure. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
0
26
1
2
Order By: Relevance
“…First, the risk profile of the patients might affect the results of the subgroup analyses. Although the superiority and inferiority of the on‐pump and off‐pump CABG surgeries have been debated, 21 patients who received off‐pump CABG surgery tend to be at a higher risk than those who received on‐pump CABG surgery 28 . It suggested that patients who received on‐pump CABG surgery in our study might have a higher risk for 30‐day mortality than those who received off‐pump CABG surgery.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…First, the risk profile of the patients might affect the results of the subgroup analyses. Although the superiority and inferiority of the on‐pump and off‐pump CABG surgeries have been debated, 21 patients who received off‐pump CABG surgery tend to be at a higher risk than those who received on‐pump CABG surgery 28 . It suggested that patients who received on‐pump CABG surgery in our study might have a higher risk for 30‐day mortality than those who received off‐pump CABG surgery.…”
Section: Discussionmentioning
confidence: 75%
“…The results of the Cox regression and logistic regression analyses are presented as hazard ratios (HRs) with 95% confidence intervals (CIs) and odds ratios (ORs) with 95% CIs. Finally, we performed subgroup analyses according to the intraoperative CPB use because the mortality and morbidity are reportedly different between off‐pump and on‐pump CABG surgery 21 . Log minus log plots were used to confirm that the central assumptions of the Cox regression models had been satisfied and that no multicollinearity existed between all variables in the two multivariable models with a variance inflation factor <2.0.…”
Section: Methodsmentioning
confidence: 99%
“…All the evidence discussed above indicate that chaperones are actively secreted from stressed cells or released from damaged cells during chronic and acute cardiac insults or during clinical procedures like coronary artery bypass graft (Westaby, 1987;Levy and Kelly, 1993;Szerafin et al, 2008;Khan et al, 2014). Of note, the global inhibition of chaperone functions in heart using small molecules able to cross the plasma membrane would be seriously harmful, since chaperones are crucial in maintaining cardiomyocyte proteostasis and in sustaining heart function both in healthy conditions and during pathological insults (Willis et al, 2009;Willis and Patterson, 2013;Tarone and Brancaccio, 2014;Sorge and Brancaccio, 2016;Penna et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The first instance of CABG was introduced in the early 20th century by Alexis Carrel in canine models. 8 As the years passed, surgeons successfully performed the first CABG procedure in humans in the 1960s. Various surgeons, since then have experimented and perfected the procedure to improve the safety and efficacy.…”
Section: Conventional Cabg Surgerymentioning
confidence: 99%
“…12 In the last decade, advancements in the field of cardiovascular surgery has led to the advent of off-pump coronary artery bypass grafting (OPCAB). 8 This procedure does not require the establishment of CPB and can be performed on the beating heart, thus in theory reducing the complications associated with CPB. 11 Historically, OPCAB was used before on-pump techniques; however, it gained popularity only in recent years.…”
Section: Conventional Cabg Surgerymentioning
confidence: 99%